2016
DOI: 10.3892/etm.2016.3679
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and oral health behaviors: The 2008–2010 Korea national health and nutrition examination survey

Abstract: Abstract. Socioeconomic status (SES) has been reported to be associated with oral health behavior. Therefore, the present study was conducted to assess the relationship between SES and oral health behaviors in a large sample of the Korean population. Data from the Korea National Health and Nutrition Examination Survey, which was conducted between 2008 and 2010 by the Division of Chronic Disease Surveillance under the Korea Centers for Disease Control and Prevention and the Korean Ministry of Health and Welfare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 32 publications
2
44
2
10
Order By: Relevance
“…A positive education gradient in never drinking and an inverse education gradient in hazardous drinking have been observed among Sri Lankan men . In contrast to the findings of Park et al, education disparities were not observed in relation to frequency of tooth brushing, and the discrepancy between that and the present study could be due to the differences in defining and categorizing tooth brushing frequency.…”
Section: Discussioncontrasting
confidence: 99%
“…A positive education gradient in never drinking and an inverse education gradient in hazardous drinking have been observed among Sri Lankan men . In contrast to the findings of Park et al, education disparities were not observed in relation to frequency of tooth brushing, and the discrepancy between that and the present study could be due to the differences in defining and categorizing tooth brushing frequency.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to causing pain and discomfort, tooth decay can expose a tooth to further infection, and several clinical studies have reported a positive correlation with an increased mortality risk in individuals with poor oral health (Jansson, Lavstedt, & Frithiof, 2002; Kim, Baker, Davarian, & Crimmings, 2013). A significant relationship has also been demonstrated between poor oral health and low socioeconomic status in numerous modern studies across the world (Chandra Shekar & Reddy, 2011; Dye & Thornton‐Evans, 2010; Hobdell et al, 2003; Park, Han, Park, & Ko, 2016; Paula et al, 2012). It is clear from the current study that the poor in mid‐nineteenth‐century Ireland also suffered from oral health problems.…”
Section: Discussionmentioning
confidence: 97%
“…Conforme observado em diversos estudos 10,36,37 , as desigualdades socioeconômicas e geográficas influenciam as condições de saúde bucal. Portanto, tais fatores deveriam ser considerados quando se avalia o desempenho dos serviços de saúde.…”
Section: ▄ Discussãounclassified